Logika dan Rasionalitas dalam Ilmu serta Implikasinya dalam Pengambilan Keputusan Sebagai Pemimpin: Systematic Literature Review - Aninda, Lovi (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to analyze the influence of logic and rationality in science that can influence a leader in making decisions. Rationality is often the basis for humans in thinking and will affect human actions based on their reasoning and logic so that it does not rule out the possibility that a statement will be considered true if it is in accordance with their logic. Through this literature analysis, I reviewed fifteen journals to add insight into the existence of logic and rationality in science and how its implications for one's leadership. The results of this study show that Rationality has an important role that can be used as a benchmark of knowledge itself and logic has four principles such as analogy, syllogism, inductive and deductive that can be used as a reference for researchers in developing new knowledge. I hope the role and influence of logic and rationality in science both in economics, law, sociology and other sciences is expected to add benefits to all elements.